The Temple : its ministry and services - Edersheim, Alfred, 1825-1889 (Peabody, Mass. : Hendrickson, 1994)
Citations from scripture, rabbinic sources, and the works of Philo and Josephus enhance the reader's understanding of the temple, its sacrifices, ministry, personnel, and services. These materials complement Edersheim's discussion, clarify difficult passages, and illumine the reader as to the true, spiritual meaning of the temple and its services. This edition brings a wealth of information together in the margins, providing a unique entree into the primary sources of the ancient world
A first view of Jerusalem, and of the temple -- Within the holy place -- Temple order, revenues, and music -- The officiating priesthood -- Sacrifices: their order and their meaning -- The burnt-offering, the sin and trespass offering, and the peace offering -- At night in the temple -- The morning and the evening sacrifice -- Sabbath in the temple -- Festive cycles and arrangement of the calendar -- The Passover -- The Paschal feast and the Lord's supper --
Reissue of a work originally published in 1874 with title: The Temple : its ministry and services as they were at the time of Jesus Christ
Includes bibliographical references and indexes
Keywords: Temple of Jerusalem (Jerusalem); Worship in the Bible; Judaism